Economic integration : theoretical assumptions and consequences of European unification - Sannwald, Rolf.; Stohler, Jacques (Princeton, N.J. : Princeton University Press, 1959)
This publication deals with a theme whose aspects were developed in a continuous exchange of opinion with the experts of the high authority of the European Coal and Steel Community
Bibliographical footnotes.
osc 07/11/2018
Loans
Keywords: European federation; Europe